A matter of time: Temporal variation in the introduction history and population genetic structuring of an invasive lizard. Issue 3 (1st June 2015) - Moule, Hannah; Chaplin, Kirilee; Bray, Rebecca D.; Miller, Kimberly A.; Thompson, Michael B.; Chapple, David G.
Abstract: Invasive species are considered one of the greatest threats to native ecosystems, second only to habitat loss and fragmentation. Despite this, the temporal dynamics of invasions are poorly understood, with most studies focusing on a single time point, providing us with only a snapshot of the biology and genetics of the invader. We investigated the invasion of Lord Howe Island by the delicate skink Lampropholis delicata and assessed the introduction history and genetic structure of this species over a 5-year period. Using genetic data taken from 2007, and again in 2011/12, we examined changes in the population genetic structure (whether new haplotypes had been introduced to the island, and shifts in haplotype frequencies) of the species on the island between these two time points. No new haplotypes were introduced to the island between 2007 and 2011/12; however, significant shifts in haplotype frequencies across the island were detected. We conclude that the delicate skink is expanding its range into the southern regions of the island and that the haplotype frequencies on Lord Howe Island are still in a state of highly dynamic flux. Our study highlights the importance of considering invasions as dynamic and studying them in such a way that enable us to better manage their impacts.